RNA modification in Cajal bodies. Issue 6 (3rd June 2017) - Meier, U. Thomas
ABSTRACT: Aside from nucleoli, Cajal bodies (CBs) are the best-characterized organelles of mammalian cell nuclei. Like nucleoli, CBs concentrate ribonucleoproteins (RNPs), in particular, spliceosomal small nuclear RNPs (snRNPs) and small nucleolar RNPs (snoRNPs). In one of the best-defined functions of CBs, most of the snoRNPs are involved in site-specific modification of snRNAs. The two major modifications are pseudouridylation and 2′-O-methylation that are guided by the box H/ACA and C/D snoRNPs, respectively. This review details the modifications, their function, the mechanism of modification, and the machineries involved. We dissect the different classes of noncoding RNAs that meet in CBs, guides and substrates. Open questions and conundrums, often raised and appearing due to experimental limitations, are pointed out and discussed. The emphasis of the review is on mammalian CBs and their function in modification of noncoding RNAs.